Simulator Panel Surya Ekonomis untuk Pengujian MPPT pada Kondisi Berbayang Sebagian - Novie Ayub Windarko; Mochamad Ari Bagus Nugroho; Muhammad Nizar Habibi; Eka Prasetyono (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
This paper describes a low-cost solar panel simulator for Maximum Power Point Tracking (MPPT) method testing, especially under partially shading conditions. The simulator consists of a DC power supply and a solar panel. The simulator works to emulate the characteristics of solar panels without depending on artificial illumination or sunlight. The simulator can represent the needed irradiation through the settings on the DC power supply. The experimental setup is developed to emulate the characteristics of solar panels at Standard Test Conditions (STC) irradiation conditions as well as varying irradiation conditions. Testing is done to emulate irradiation varies from 200-1,000 W/m2. To emulate the characteristics of solar panels in partial shading conditions, two DC power supply units and two solar panels are used. Each solar panel is simulated to receive different solar irradiations. The test results show that the simulator can emulate the characteristics of solar panels under partial shading conditions which has several maximum power points. Furthermore, partial shading conditions are simulated under varying irradiation conditions which resulted varying maximum power point values.